A framework for site informed light art installations - Mercado, Nicholas (Kansas State University, 2015)
The purpose of this study is to investigate and design public light art installations. The investigation consisted of evaluating select examples of public light installations in order to develop a typology, and designing two site-specific light art installations: one in Wichita, Kansas, and the other, in Denver, Colorado. Though public light art is found in most cities, its potential is often lost or unrecognized. In certain cases, public light art can be ‘plop art,’ which is plopped senselessly without much regard to context or experiential qualities. This project seeks to explore the different types of public light art and to find what approach or qualities should be considered when designing public light art. My approach can be described as artistic research. The methods include an apprenticeship to an artist, a precedent study, development of a light typology, an analysis of site and context, establishing a design matrix for two design projects, and an iterative process of making. Each of these methods were undertaken in order to effectively address my research question: What type of public light art is most appropriate for a specific site and how does it relate to creative placemaking? This project overlaps with a collective project group entitled Creative Place-Making, which is comprised of other fifth-year master of landscape architecture students with an underlying interest in art and design as place-making tools. Each student in the group addressed the site in Wichita, Kansas in a unique way. I addressed this site as a temporary landscape, creating an interactive light installation intended to be in place up to five years. In contrast, I addressed the Denver, Colorado site as a long term landscape, and designed a sculptural illuminating gateway. Each of these light art installations were informed by a particular set of characteristics that make each design site-specific.
Keywords: Landscape architecture; Public art; Creative placemaking; Light installation; Site informed; Installation; Landscape Architecture (0390)